The effect of current strength on tensile strength and impact toughness of cast iron welded joints - Wijoyo Wijoyo; Mujahid Mujahid; Achmad Nurhidayat; Eko Surjadi; Iman Saefuloh (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Cast iron is a high-carbon iron-carbon alloy. Cast iron is difficult to weld because of the high carbon concentration. A good connection necessitates the application of specific strategies and processes. This study investigates the effect of current strength on the mechanical properties of tensile strength and impact toughness of cast iron welded joints. The main materials used are gray cast iron and CIN 3 filler. The welding process uses an AC TIG welding machine. The welding seam is made of a single V with an angle of 70o, and the electric current variations are 80A, 90A, and 100A, respectively. Tensile testing is carried out with a UTM machine referring to ASTM E8M, while the Charpy impact test refers to ASTM E23. From the study results, it was found that the higher the use of electric current resulted in the mechanical properties of the tensile strength and impact toughness of the weld being also higher, which occurred at 100A electric current, reaching 181.05 MPa and 0.22 J/mm2. Besi cor merupakan paduan antara besi dan karbon di atas 2.5%. Kadar karbon yang tinggi ini menyebabkan besi cor sulit untuk dilas. Perlu teknik dan proses tertentu untuk mendapatkan sambungan yang baik. Penelitian ini bertujuan menyelidiki pengaruh kuat arus terhadap sifat mekanik kekuatan tarik dan ketangguhan impak sambungan las besi cor. Bahan utama yang digunakan adalah besi cor kelabu dan filler CIN 3. Proses pengelasan menggunakan mesin las TIG AC. Kampuh las dibuat V tunggal bersudut 70o, variasi arus listrik berturut-turut adalah 80A, 90A dan 100A. Pengujian tarik dilakukan dengan mesin UTM mengacu pada ASTM E8M, sedangkan pengujian impak charpy mengacu pada ASTM E23. Dari hasil penelitian didapatkan, pemakaian arus listrik semakin tinggi mengakibatkan sifat mekanik kekuatan tarik dan ketangguhan impak hasil lasan juga semakin tinggi, yaitu terjadi pada kuat arus listrik 100A, mencapai 181.05 MPa dan 0,22 J/mm2.